Guiding The Readings Of The Names In Surah Ghafir Through Fath Al-Bayan: A Grammatical And Semantic Study/ توجيه قراءات الأسماء في سورة غافر من كتاب فتح البيان نحويَّا وبلاغيًّا - Mohamed Bakhet, Mohamed Ibrahim; Maghawry Mohamed, Abdelkarim Ahmed; El-Sharkawy, Mohammed Shehata Abdel-Hamid; Issa, Koussoube; Nasirudeen, Abdulwasiu Isiaq (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This is a study in grammatical and morphological studies that revolves around grammatical and morphological guidance and an explanation of the rhetorical significance of the readings of Quranic names in Surat Ghafir from the book “Fath al-Bayan fi Maqasid al-Qur’an” by Imam al-Siddiq Hasan Khan (d. 1307 AH). The researchers followed a methodology of determining the readings of the names in the Holy Surah, collecting them, and studying them grammatically and rhetorically by explaining the type of readings contained in the Holy Surah, describing Imam al-Siddiq’s method in presenting them, highlighting his approach and process in these directions, then studying his grammatical and morphological directions for the readings and comparing them with the directions of grammarians, and showing the effect of the different readings on the general meaning of the verses. The researchers in this study followed a set of research methods, including the inductive and statistical methods, where the readings were collected in the names. The descriptive approach was used to describe and clarify the circumstances of the readings. Then, they analyzed this information and revealed its grammatical and rhetorical benefits and connotations according to the analytical approach. The researchers concluded a set of results, the most important of which are: The Sheikh relied in his testimonies on the Holy Qur’an and its readings and the words of the Arabs in poetry and prose, and he did not cite the hadith of the Holy Prophet in directing him to the Qur’anic readings, and that he sometimes chose to read with the strength of the face expressive in the meaning to take it from other aspects, and the Qur’anic readings represent a great linguistic wealth, containing many grammatical rulings and multiple dialectical phenomena, and the research revealed the ability of Imam Al-Qanuji to direct the Qur’anic readings, which indicates his skillful competence. In this direction, these and other results are consistent with and answer the questions raised and answered by the research.